2004
DOI: 10.1038/nbt1003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and ultra-sensitive determination of enzyme activities using surface-enhanced resonance Raman scattering

Abstract: Measurement of enzyme activity and selectivity at in vivo concentrations is highly desirable in a range of fields including diagnostics, functional proteomics and directed evolution. Here we demonstrate how surface-enhanced resonance Raman scattering (SERRS), measured using silver nanoparticles, can be used to detect the activity of hydrolases at ultra-low levels. This approach was made possible by designing 'masked' enzyme substrates that are initially completely undetected by SERRS. Turnover of the substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(125 citation statements)
references
References 29 publications
2
121
0
Order By: Relevance
“…Thus SERRS has been used to study heme proteins, 9 to study the mechanism of electron transfer in cytochromes, 10 and more recently for trace detection of DNA 11,12 and enzyme activity. 13 The sensitivity of SERRS exceeds that of fluorescence, which is currently the most prolific technique employed for studying biomolecules, as proven theoretically 14 and experimentally. 15 SER(R)S has another immense advantage over fluorescence in that the signals have extremely small line-widths compared to the broad spectra of fluorescence emission; and hence it is possible, using SER(R)S labels, to carry out multiplexed detection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus SERRS has been used to study heme proteins, 9 to study the mechanism of electron transfer in cytochromes, 10 and more recently for trace detection of DNA 11,12 and enzyme activity. 13 The sensitivity of SERRS exceeds that of fluorescence, which is currently the most prolific technique employed for studying biomolecules, as proven theoretically 14 and experimentally. 15 SER(R)S has another immense advantage over fluorescence in that the signals have extremely small line-widths compared to the broad spectra of fluorescence emission; and hence it is possible, using SER(R)S labels, to carry out multiplexed detection.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a type of SERS-active substrate with uniformly large and highly reproducible Raman-enhancing power has been developed by growing Ag nanoparticles on arrays of anodic aluminum oxide (AAO) nanochannels to take advantage of the sub-10-nm inter-particle gaps, which act as 'hot junctions' for creating the electromagnetic enhancement 4 . The high sensitivity and reproducibility of such a substrate-hereafter referred to as Ag/AAO-SERS substrate-facilitated the use of SERS for chemical/biological sensing applications [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . SERS of various types of bacteria including Gram-positive, Gram-negative and mycobacteria have been acquired and the response of bacteria to antibiotics has been examined 21 .…”
mentioning
confidence: 99%
“…[76] SERS can be used to enhance native Raman signals, by close proximity to roughened metal surfaces. However, perhaps the more promising application is to probe for specific interactions, for example by detection of specific antigens [37] or enzyme activity [18,77]. Kneipp et al[78] demonstrated the use of SERS to enhance Raman signals in single cells, therefore decreasing the acquisition time for a single map significantly.…”
Section: An Alternative Technique -Surface Enhanced Raman Spectroscopmentioning
confidence: 99%
“…[37,[80][81][82] SERRS based assays have also been used to detect enzyme activity. Moore et al [77] designed an assay to detect a variety of enzyme activities including from lipases, esterases and proteases. In these assays, a substrate consisting of a recognition site for a particular enzyme, a linker that can be cleaved by the particular enzyme and a SERRS-active dye was synthesised.…”
Section: An Alternative Technique -Surface Enhanced Raman Spectroscopmentioning
confidence: 99%